Intersection of social vulnerability and residential diversity: Postoperative outcomes following resection of lung and colon cancer. Issue 5 (1st July 2021) - Diaz, Adrian; Dalmacy, Djhenne; Hyer, J. Madison; Tsilimigras, Diamantis; Pawlik, Timothy M.
Abstract: Introduction: While the impact of demographic factors on postoperative outcomes has been examined, little is known about the intersection between social vulnerability and residential diversity on postoperative outcomes following cancer surgery. Methods: Individuals who underwent a lung or colon resection for cancer were identified in the 2016–2017 Medicare database. Data were merged with the Centers for Disease Control and Prevention social vulnerability index and a residential diversity index was calculated. Logistic regression models were utilized to estimate the probability of postoperative outcomes. Results: Among 55 742 Medicare beneficiaries who underwent lung (39.4%) or colon (60.6%) resection, most were male (46.6%), White (90.2%) and had a mean age of 75.3 years. After adjustment for competing risk factors, both social vulnerability and residential diversity were associated with mortality and other postoperative outcomes. In assessing the intersection of social vulnerability and residential diversity, synergistic effects were noted as patients from counties with low social vulnerability and high residential diversity had the lowest probability of 30‐day mortality (3.2%, 95% confidence interval [CI]: 3.0–3.5) while patients from counties with high social vulnerability and low diversity had a higher probability of 30‐day postoperative death (5.2%, 95% CI: 4.6–5.8; odds ratio: 1.02, 95% CI: 1.01–1.03). Conclusion: Social vulnerability and residential diversity were independently associated with postoperative outcomes. The intersection of these two social health determinants demonstrated a synergistic effect on the risk of adverse outcomes following lung and colon cancer surgery.